The Role of Additionality in the EU Cohesion Policies: An Example of Firm-Level Investment Support - Andries Brandsma; Pavel Ciaian; d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2010)
Additionality is one of the key principles driving the functioning of the EU Cohesion Policies (ECP). The present paper studies how additionality affects the distributional effects of the ECP. Using the example of the firm-level investment support, we analyse the role of additionality and co-financing rate in differently competitive markets. We find that the investment additionality and the level of competition importantly affect the distributional effects of the ECP. Imposing additionality to the ECP investments in a perfectly competitive environment causes distortions in the capital market and leads to lower welfare levels. In contrast, without the enforcement of additionality, the distortions are zero and the support fully benefits firms. In an imperfectly competitive environment the firm-level investment support may increase capital use and may be welfare increasing with and without the enforcement of the investment additionality.
Keywords: F1; O1; R3; R4; 330; Additionality; EU Cohesion Policy; investment subsidy; regional development